PENINGKATAN PENDAPATAN MELALUI PENANAMAN TANAMAN SELA KEDELE DAN CABE RAWIT DIANTARA TANAMAN PANILI YANG BELUM MENGHASILKAN - Asnaw, Robet; Arief, Ratna Wylis (Publikasi Penelitian Terapan dan Kebijakan, 2010)
Low production and low quality of vanilla caused by the farmers do not cultivate the plant in proper way, such as pruning the post, mound, fertilizer, and post harvest technology. Besides, monoculture farming system espesially for young plant caused does not have affort. The activity of assesment adaptability of package technology and farming system of vanilla was conducted at Jabung (East Lampung) in 2007. The treatments were Model 1 (recommended cultivation technology) such as superior variety of Anggrek vanilla, pruning the post, mound, and fertilizer, and Model 2 (traditional cultivation technology). Farming system of vanilla (vanilla-soybean and vanilla-chili) will be done by young plant of vanilla. The objective was to increase farmers income and to obtain technology packages cultivation and farming system exspecially for young plant of vanilla. The result showed that cultivar Anggrek vanilla that support by application of recommended cultivated technology such as prunning andfertilizer produced higher growth than local cultivar. Soybean and chilli were planted among vanilla result the same growth and production with soybean monoculture and chilli monoculture. Soybean planted among vanilla (pattern of vanilla-soybean) increased farmers income average Rp.1.691.000,- per ha per season (3 months) and increased farmers income average Rp. 1.656.000,- per ha per season (3 months) by pattern of vanilla-chili.